(untitled) (UTM Press - Edited Book, 2023)
Embark on a profound exploration of biomass’s transformative potential through the lens of "Sustainable Innovations in Biomass Transformation to Chemicals, Fuels, and Materials." This comprehensive compilation, divided into ten chapters, serves as a guidepost directing the future trajectory of research and development in lignocellulosic resources. Chapter 1 provides overview of biomass conversion. Chapter 2 unveils the promising realm of biomass-derived alkyl levulinates as biofuel additives, offering insights into their vast potential. Chapters 3 and 4 explore into the intricacies of microwave-assisted pyrolysis and the characteristics of biochar produced through this revolutionary process. Chapter 5 unravels the extraction and application of nanocellulose from biomass. Chapter 6 introduces the synthesis of carboxymethyl cellulose, a product of the OzBiONY process—an innovative biomass pre-treatment. Chapter 7 delves into the detailed transformation of glycerol to olefins. In Chapter 8, unravelling the intricacies of biogas production from palm oil mill effluent and pineapple peel wastes. Chapter 9 emphases on the conversion of agricultural waste for biomaterial development. The final chapter tackles optimization, exploring ozonolysis pre-treatment using response surface methodology and artificial neural networks. This book serves as a guidebook for technologies in biomass pre-treatment and processing strategies, offering insights applicable to lignocellulosic biorefineries. This anthology is more than a book; it’s a catalyst for a sustainable future, inviting readers to uncover invaluable content and spark collaborations that will shape the landscape of biomass innovation. Welcome to a journey where knowledge and innovation meet collaboration, and the future of biomass transformation unfolds.